The Yield Volume Fraction approach to the description of the stress-strain curve of a nickel-base superalloy - Chen, J; Korsunsky, AM (2022)
The stress-strain curves of most metallic alloys are often described using the relatively simple Ramberg-Osgood relationship. Whilst this description captures the overall stress-strain curve under monotonic tensile loading with reasonable overall accuracy, it often presents significant errors in the immediate post-yield region where the interplay between the elastic and plastic strains is particularly significant. This study proposes and develops a new approach to the description of the tensile stress-strain curve based on the Yield Volume Fraction (YVF) function. The YVF description provides an excellent match to experimental stress-strain curves based on a physically meaningful parameter that corresponds to the cumulative volume fraction of the polycrystal that undergoes yielding during monotonic deformation. The statistical nature of the polycrystal yield phenomenon is highlighted by the fact that the YVF model achieves good agreement with observations when the lognormal and extreme value distributions are employed to express the cumulative density function for the total yield volume fraction, and the probability density function for the incremental yield volume fraction, respectively. This proposed approach is compared with crystal plasticity finite element (CPFE) simulations and the Ramberg-Osgood model, along with experimental observations. The results highlight the potential of more extensive use of statistical methods in the description of material deformation response for improved design.